Levantamento da produção de teses e dissertações sobre autoeficácia docente para ensinar educação física na escola (2005-2015) - Nunes, Ana Estela [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
The current Physical Education national and international scenarios have been marked by several challenges for the professionals who work in it. Students unmotivated for participating in the classes is one of them, making more complex the task of teaching and also, putting in check the teacher's capability. A lens that can help to investigate this phenomenon is the social cognitive theory, more specifically the teacher self-efficacy beliefs. Thus, there is the need to gather information from the literature about this theme related to the theory, in order to have an overview of what has been produced in different contexts. The present study had the goal to search the knowledge production about the teacher self-efficacy to teach Physical Education at schools. To do so, the search was made to gather dissertations and thesis in the databases BDTD, BDTDCapes and ProQuest between 2005 and 2015. The terms used were autoeficácia docente, educação física escolar, autoeficácia e ensino, teachers' self-efficacy, physical education classes and, teaching selfefficacy. After using stablished criteria, eight works were selected in total, being four North Americans, and four Brazilian. The measurements of teachers self-efficacy levels and the identification of their sources were the main objective in the selected studies. The methodologies had the predominance of quantitative, followed by the mix and, only one study used qualitative approach. Main results of the selected studies found medium/high levels of teacher self-efficacy and, enactive mastery and social persuasion were the sources with biggest influence upon the beliefs. These results show an overview of the research that have been carried out within the teacher self-efficacy and, have pointed out to the need of to expand the development of the research in Brazilian context

O ensino da Educação Física atual nos cenários nacional e internacional tem sido marcado por diversos desafios para os docentes que nela atuam. A desmotivação discente na participação das aulas é um deles, tornando mais complexa a tarefa de ensiar e fazendo com que o professor questione a própria capacidade docente. Uma das lentes que ajudam na leitura desse fenômeno está atrelada à teoria social cognitiva, mais especificamente, às crenças de autoeficácia docente. Desta forma, encontrou-se a necessidade de reunir informações da literatura a respeito deste tema atrelado à teoria, a fim de se ter um panorama do que tem sido produzido em variados contextos.O presente estudo teve como objetivorealizar um levantamento da produção de conhecimento sobre a autoeficácia docente para ensinar Educação Física na escola. Para isso, foi feito um levantamento de teses e dissertações nas bases de dados BDTD, BTDCapes e ProQuest entre o período de 2005 a 2015. Os termos utilizados foram autoeficácia docente, educação física escolar, autoeficácia e ensino, teachers' self-efficacy, physical education classes, teaching self-efficacy. Após a aplicação dos critérios estabelecidos, oito trabalhos foram selecionados no total, sendo quatro norteamericanos e quatro brasileiros.A mensuração dos níveis de autoeficácia docente e a identificação de suas fontes foram os principais objetivos nos estudos selecionados. Em termos de metodologias, houve o predomínio da quantitativa, seguida pela mista, sendo queapenas um trabalho utilizou-seda qualitativa. Como principais resultados dos estudos selecionados encontrou-se níveis altos/médios de autoeficácia dos professores e, experiências diretas e persuasão social como as fontes de maior ... (Resumo completo, clicar acesso eletrônico abaixo)
Keywords: Educação física - Estudo e ensino; Revisão; Professores de educação fisica; Auto-eficácia